Analysis of adolescents’perspectives on the role of guidance and counseling - Minarsi Minarsi; Deby Angeta Sari; Dinar Nur Sagita; Tiana Febriani; Sindi Fitriana (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
The perspective of adolescents is important because it affects the extent to which guidance and counseling services are beneficial to them. The effectiveness of guidance and counseling services heavily relies on how adolescents perceive the role of these services. Various studies indicate that adolescents' perspectives on guidance and counseling services are often lacking, necessitating further examination of their views on participation in such programs. This article aims to explore adolescents' perspectives on the role of guidance and counseling. The research method employs a descriptive approach with qualitative methods. Data collection involves observation, interviews, and documentation. The subjects of this study are individuals in the adolescent development stage, selected through random sampling. The results show that adolescents predominantly have a positive perspective towards guidance and counseling, as evidenced by the numerous sources agreeing that these services are important for them. Adolescents tend to view guidance and counseling as a source of guidance, advice, and direction that helps them resolve their issues.